The tin mines of the Waterberg (Transvaal), 1905-1914 - Gail Nattrass (Contree, 2024)
Tin mining in the Transvaal district of the Waterberg between 1905 and 1914 occurred mainly at Rooiberg, Zaaiplaats and Union Tin. The focus of this article is on Rooiberg, which reflects the general conditions experienced in all three mining centres. Problems such as the remoteness of the mines and the unpredictable nature of the tin deposits contributed to the difficulties of drawing and maintaining the skilled and unskilled labour force required. Apart from imported labourers (such as Chinese and Hereros), the tin mining companies employed poor whites to supplement their unskilled labour force. This gave rise to the unusual set of socio-economic conditions which are explored in this article.